2011
DOI: 10.1007/s11164-011-0365-0
|View full text |Cite
|
Sign up to set email alerts
|

The photocatalytic properties of amorphous TiO2 composite films deposited by magnetron sputtering

Abstract: The preparation of amorphous TiO 2 film coupled with various metaloxide semiconductors and their photocatalytic activities evaluated by photodegradation of methylene blue and rhodamine B aqueous solution are briefly reviewed. The proposed photoreaction mechanism of the amorphous composite semiconductor and the differences between amorphous TiO 2 -based films and crystalline TiO 2 photocatalytic materials in terms of preparation and usage are addressed. The inactive intrinsic amorphous TiO 2 film coupled with v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…When the electrons and holes reach the surface, these react with adsorbed molecules (e.g., water, molecular oxygen) and trigger the production of very reactive radicals (OH•, O 2 • − ), which are responsible for the degradation of organic compounds into CO 2 and H 2 O . According to these results, it was reasonable to hypothesize that the short‐range of TiO 2 molecular arrangement in amorphous hybrid films could induce a similar basic energy band structure of crystalline TiO 2 . Thus, the band theory of crystalline TiO 2 might be applicable to amorphous TiO 2 .…”
Section: Resultsmentioning
confidence: 98%
“…When the electrons and holes reach the surface, these react with adsorbed molecules (e.g., water, molecular oxygen) and trigger the production of very reactive radicals (OH•, O 2 • − ), which are responsible for the degradation of organic compounds into CO 2 and H 2 O . According to these results, it was reasonable to hypothesize that the short‐range of TiO 2 molecular arrangement in amorphous hybrid films could induce a similar basic energy band structure of crystalline TiO 2 . Thus, the band theory of crystalline TiO 2 might be applicable to amorphous TiO 2 .…”
Section: Resultsmentioning
confidence: 98%
“…It is known that transition metals (W, V, Ag, Cu etc.) or non-metals (S, C, N ) doped TiO has a lower band gap than pure TiO and can be used to increase the production of reactive oxygen species (ROS) under visible light irradiation in solutions containing undesired pollutants Fujishima et al (2008), Huang et al (2012). Doped with silver, TiO nanoparticles (NPs) prepared by sol-gel technique were successfully applied for deactivation of different microorganisms (Escherichia coli, Pseudomonas aeruginosa, Bacillus subtilis and Staphylococcus aureus).…”
Section: Introductionmentioning
confidence: 99%
“…According to Zhu et al (2013), Wu et al (2014), Cu as an essential trace element participating in a variety of metabolic activities in living organisms, might be a more effective antimicrobial agent than Ag due to its low cytotoxicity. According to Norambuena et al (2016), amongst metals with antibacterial properties, copper has shown superior in vitro antibacterial performance while maintaining an acceptable cytotoxicity profile. A thin film containing copper could prevent early formation of biofilm which limits periprosthetic infections.…”
Section: Introductionmentioning
confidence: 99%
“…Titanium dioxide has been utilized for many years in a variety of applications, including pigmentation, a protective chemical in sunscreen , water treatment , air purification , deodorization, and sterilization . One of the most exciting attributes of TiO 2 is its photocatalytic ability.…”
Section: Introductionmentioning
confidence: 99%